Molecular Breeding for Nutritionally Enriched Maize: Status and Prospects - Prasanna, Boddupalli M.; Palacios-Rojas, Natalia; Hossain, Firoz; Muthusamy, Vignesh; Menkir, Abebe; Dhliwayo, Thanda; Ndhlela, Thokozile; San Vicente, Felix; Nair, Sudha K.; Vivek, Bindiganavile S.; Zhang, Xuecai; Olsen, Mike; et al. (Frontiers in Genetics, 2020)
Maize is a major source of food security and economic development in sub-Saharan Africa (SSA), Latin America and the Caribbean, and is among the top three cereal crops in Asia. Yet, the traditional maize mainly consumed by millions of resource-poor is deficient in certain essential amino acids, vitamins and minerals. Biofortified maize cultivars enriched with essential minerals and vitamins could be particularly impactful in rural areas with limited access to dietary supplements and fortified foods. Significant progress has been made in developing, testing, and deploying maize cultivars biofortified with quality protein maize (QPM), provitamin A, and kernel zinc. In this review, we outline the status and prospects of developing nutritionally enriched maize by successfully harnessing conventional and molecular marker-assisted breeding, and highlights the need for intensification of efforts to create greater impacts on malnutrition in maize-comsuming populations, especially in the developing world.